Recognition of a monoclonal antibody against a small molecular weight antigen by monitoring the antigen–antibody reaction using fluorescence labeled structured peptides. Issue 3 (1st February 2015) - Tominaga, Yuki; Hirata, Akiyoshi; Nokihara, Kiyoshi
Graphical abstract